ANALYSIS OF THE SYNERGY OF TOURISM OF BANYUWANGI TRADITION FROM A PERSPECTIVE OF WELFARE AND SUSTAINABILITY: ANALISIS SINERGITAS KEPARIWISATAAN TRADISI BANYUWANGI PERSPEKTIF KESEJAHTERAAN DAN BERKELANJUTAN - Safrieta Jatu Permatasari; Herwin Kurniad; Muhammad Rendy Agung Octaviyanto; Henny Listyastuti (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to analyze the implementation of tourism development policies based on mystical traditions in Banyuwangi Regency as an integrative model between cultural preservation, local spirituality, and improving community welfare. In the context of modernization and globalization, the mystical tradition of the Banyuwangi people continues to survive through innovative policies of the local government that place local culture as the main axis of sustainable development. The approach of this research is qualitative participatory with in-depth interviews, field observations, and analysis of regional tourism policy documents and programs. The results of the study show that tradition-based tourism policies have integrated the mystical and spiritual values of the Using community into the form of cultural festivals such as Gandrung Sewu, Seblang, and Barong Ider Bumi. The innovation of the Banyuwangi Regency Government has succeeded in increasing community participation, strengthening cultural identity, and encouraging local economic growth. Policy success is influenced by close collaboration between governments and indigenous peoples, with the application of participatory, inclusive, and non-discriminatory principles. However, challenges were found in the form of potential cultural commercialization and economic benefit gaps. It is concluded that tradition-based tourism development policies in Banyuwangi present conceptual and practical novelty through the integration of mystical values in sustainable development strategies. This model shows a balance between cultural preservation and improving community welfare that is linear with the principles of the SDGs and Asta Cita's vision.